Kajian Korosi Struktur Conveyor C Pada Tambang Batubara PT XYZ Di Kabupaten Bungo, Provinsi Jambi - Mohamad Rifki Alghifari (Jurnal Riset Teknik Pertambangan, 2021)
Abstract. Conveyor structure is a tool that is applied to the mining industry as a tool that supports the process of moving excavated materials such as coal. The structure of the conveyor is made of steel which is subject to corrosion. The disadvantage of corrosion is that it results in a reduction in the thickness of the conveyor structure. Therefore, it is necessary to control and monitor corrosion on the conveyor structure to be observed, so that corrosion can be controlled. The purpose of this study was to determine the type of corrosion, corrosion control methods, and thickness reduction. The methodology used in this study is measuring the thickness reduction of the conveyor structure. This research was conducted on a 60 meter long conveyor structure above ground level. Measurement of the thickness of the conveyor structure using the Ultrasonic Thickness Gauge TT 130 at 16 observation points. The environmental conditions in the research area are the air temperature in the range of 27oC-29oC, while the rainfall is in the range of 111.37-437.30 mm. The type of corrosion that occurs in the conveyor structure is uniform corrosion. In controlling this corrosion using a 3-layer coating method with a Seaguard 5000 primer coating, Sherglass FF intermediate coating, and aliphatic acrylic modified polyurethane top coating. Abstrak. Struktur conveyor adalah alat yang diaplikasikan pada industri pertambangan sebagai alat yang menunjang dalam proses pemindahan material bahan galian contohnya batubara. Struktur conveyor terbuat dari baja yang dapat mengalami korosi. Kerugian terjadinya korosi yaitu mengakibatkan pengurangan ketebalan struktur conveyor. Oleh karena itu, diperlukannya pengendalian serta monitoring korosi pada struktur conveyor yang akan diamati, sehingga korosi dapat dikendalikan. Tujuan dilakukannya penelitian ini adalah untuk mengetahui jenis korosi, metoda pengendalian korosi, dan pengurangan ketebalannya. Metodologi yang digunakan dalam penelitian ini yaitu pengukuran pengurangan ketebalan struktur conveyor. Penelitian ini dilakukan pada struktur conveyor sepanjang 60 meter yang berada di atas permukaan tanah. Pengukuran ketebalan struktur conveyor menggunakan alat Ultrasonic Thickness Gauge TT 130 pada 16 titik pengamatan. Kondisi lingkungan di daerah penelitian yaitu temperatur udara kisaran 27 oC-29oC, sedangkan curah hujan kisaran 111,37-437,30 mm. Jenis korosi yang terjadi pada struktur conveyor adalah korosi merata. Dalam pengendalian korosi ini menggunakan metoda 3 lapis coating dengan primer coating Seaguard 5000, intermediate coating Sherglass FF, dan top coating aliphatic acrylic modified polyurethane.